The Effect of Motivation, Training and Compensation on Employee Performance at the Department of Logistics - Muhammad Kosim; Prasetyo Harisandi; Fiqih Maria Rabiatul Hariroh; Purwanto Purwanto4 (President University, 2023)
The purpose of the study was to determine and analyze the effect of motivation, training and compensation on the performance of employees of PT. Hulane Pacific delta, either partially or simultaneously. The population of this study were all employees of the Engineering department at PT. Hulane Pacific delta, which numbered 10 people. The method of data collection was carried out by questionnaires and documentation studies. The data analysis model used is multiple linear regression using SPSS software. The results showed that motivation, training and Compensation had an effect on employee performance either partially or simultaneously.